1991
DOI: 10.1161/01.hyp.17.6.1104
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and the testes influence hypertension in a hybrid rat model.

Abstract: The objective of this study was to determine if males with a deficient androgen receptor would develop hypertension when crossed with a hypertensive parent Female King-Holtzman rats (n=15), heterozygous for the testicular feminization (Tfm) gene, were crossed with male spontaneously hypertensive rats (SHR), and blood pressure was measured weekly from 5-14 weeks in the F, hybrid males. Approximately 50% of the F, hybrid males were Tfm males and androgen receptor-deficient, and 50% were normal. Blood pressure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Discussion In our previous work we showed that the Y chromosome interacted with an autosomal component to increase BP 7 -8 and that the AR was necessary for the full expression of the SHR Y chromosome BP effect as well as a possible androgen effect that did not function through the AR. 8 The present research continues to support these findings and extends this work to show that the Y chromosome from a hypertensive father continues to elevate BP after 11 generations of backcrossing to normotensive mothers. The pressure difference between the pure WKY males and F n SHR/y males averaged 12 mm Hg, which can be thought of as the hypertensive Y effect against a normotensive autosomal background.…”
Section: Resultssupporting
confidence: 76%
“…Discussion In our previous work we showed that the Y chromosome interacted with an autosomal component to increase BP 7 -8 and that the AR was necessary for the full expression of the SHR Y chromosome BP effect as well as a possible androgen effect that did not function through the AR. 8 The present research continues to support these findings and extends this work to show that the Y chromosome from a hypertensive father continues to elevate BP after 11 generations of backcrossing to normotensive mothers. The pressure difference between the pure WKY males and F n SHR/y males averaged 12 mm Hg, which can be thought of as the hypertensive Y effect against a normotensive autosomal background.…”
Section: Resultssupporting
confidence: 76%
“…22 Testosterone most likely was the main steroid responsible for the blood pressure effect because castration reduced blood pressure, and testosterone replacement after castration restored blood pressure to control levels. 19,22,23 However, not as much is known about the interaction of NE and testosterone. Testosterone can influence NE metabolism, storage, and release.…”
Section: Discussionmentioning
confidence: 99%
“…The SHR has increased SNS activity 5,6,9,19 that can lead to increased circulating NE, 12,19 which has been implicated in the genesis of hypertension. The testosterone-induced increase in renal NE release (125% to 167%) was seen in both groups with an SHR Y chromosome (SHR and SHR/y animals), possibly due to increased NE stores and more release per stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sexual difference in blood pressure is present in genetically hypertensive rats, including SHR (Ely and Turner, 1990;Chen and Meng, 1991;Ely et al, 1991;Chen et al, 1992), and the Dahl salt-sensitive (Dahl et al, 1975) as well as their normotensive control strains Wistar Kyoto (Ely et al, 1991) and the Dahl salt-resistant (Rapp and Dene, 1985), respectively. It has been shown that gonadectomy retards the development of hypertension in SHR rats (Iams and Wexler, 1977;Masubuchi et al, 1982;Chen and Meng, 1991).…”
mentioning
confidence: 98%